Study of Battery Management System with analysis of Ni-mh, lithium-ion Batteries - Anesh Kshirsagar; N.B.Sambre (International Journal of Engineering and Management Research, 2023)
The conventional flooded-type lead acid battery is being replaced by the sealed-type VRLA (Valve-Regulated Lead- Acid) battery, which is superior from the standpoints of economy, reliability, safety, ease of maintenance and construction. The work on the new battery management system which automatically determines the level of deterioration of the batteries using battery parameters like voltage, charging, discharging current and temperature, and additionally, indicates the approximate charge stored and indicates time to replace a defective battery. It makes a reliable maintenance free batteries of power-supply units for telecommunication equipment and Electric vehicle or the like applications. However battery maintenance work has somedifficulties and another problem is how to manage battery for equipment such as an Electric vehicle more efficiently. So we have worked on the battery management system with higher efficiency, which monitor a state of battery and then integrates its data from battery-management unit and in future scope the battery deterioration unit will be controlled through wireless lines.